Prediction of Sediment Yield in the Middle Reaches of the Yellow River Basin Under Extreme Precipitation - Dang, Suzhen; Liu, Xiaoyan; Yin, Huijuan; Guo, Xinwei (Frontiers in Earth Science, 2020)
The Yellow River is one of the rivers with the largest amount of sediment in the world. The amount of incoming sediment has an important impact on the management of water resources in the basin, the distribution of sediment resources, and the construction of major water conservancy projects. The main source of sediment in the Yellow River Basin is the Loess Plateau in the middle reaches. Floods caused by extreme precipitation are the main driving force of soil erosion in the Loess Plateau. In this study, the main sediment-yielding area in the middle reaches of the Yellow River was used as the study area, and extreme precipitation scenarios were constructed based on the analysis of historical extreme precipitation. According to recent sediment yield indicators and the relationship between precipitation and sediment yield, the corresponding sediment yield under the current surface conditions in the study area was analyzed. The results showed thatthe areal rainfall of the constructed extreme rainfall scenario reached 159.9 mm, with a recurrence period of 460 years. The corresponding annual sediment yield of the study area under the current underlying surface conditions was 1.323 billion tons, of which the annual sediment yields in the region from Hekouzhen to Longmen (HLR), the Jinghe River Basin, the area above Tuoshi in the Weihe River Basin and the area above Liujiahe in the Beiluo River Basin were 612.8 million tons, 565.6 million tons, 108.4 million tons and 36.3 million tons, respectively. And the regions with high sediment yield capacity are the Wuding River Basin, Huangfuchuan River Basin and Jialu River Basin in the HLR and the area above Qingyang in the Jinghe River Basin.